2017
DOI: 10.1038/srep46185
|View full text |Cite
|
Sign up to set email alerts
|

Methane protects against polyethylene glycol-induced osmotic stress in maize by improving sugar and ascorbic acid metabolism

Abstract: Although aerobic methane (CH 4 ) release from plants leads to an intense scientific and public controversy in the recent years, the potential functions of endogenous CH 4 production in plants are still largely unknown. Here, we reported that polyethylene glycol (PEG)-induced osmotic stress significantly increased CH 4 production and soluble sugar contents in maize (Zea mays L.) root tissues. These enhancements were more pronounced in the drought stress-tolerant cultivar Zhengdan 958 (ZD958) than in the drought… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 58 publications
(79 reference statements)
5
21
0
Order By: Relevance
“…Similar to the response of NO, we proved that CH 4 can alleviate salinity stress and copper stress in alfalfa plants [ 8 , 40 ]. Recently, the alleviation of osmotic stress in maize seedlings by CH 4 was confirmed, and the involvement of sugar and ascorbic acid metabolism was preliminarily elucidated [ 41 ]. However, the cross-talk between CH 4 and NO signaling in plant tolerance against osmotic stress is still elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the response of NO, we proved that CH 4 can alleviate salinity stress and copper stress in alfalfa plants [ 8 , 40 ]. Recently, the alleviation of osmotic stress in maize seedlings by CH 4 was confirmed, and the involvement of sugar and ascorbic acid metabolism was preliminarily elucidated [ 41 ]. However, the cross-talk between CH 4 and NO signaling in plant tolerance against osmotic stress is still elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Under osmotic stress, not only did the sugar content in maize root tissues increase by CH 4 (exogenously applied 0.65 mM), but the sugar and AsA metabolism in maize seedlings were also regulated by CH 4 [66]. Further research found a positive role of endogenous NO in CH 4 -enhanced plant tolerance against osmotic stress in mung beans [46].…”
Section: Plant Species Abiotic Stress and Its Effect Ch 4 Roles Undermentioning
confidence: 89%
“…Alfalfa encourages CH 4 production under salt stress [65]. Han et al [66] reported that polyethylene glycol increases CH 4 production in maize. Some researchers have demonstrated that alfalfa produces CH 4 under heavy metal stress, such as from copper (Cu) [67], aluminum (Al) [13], or cadmium (Ca) [68].…”
Section: Methane (Ch 4 )mentioning
confidence: 99%
See 1 more Smart Citation
“…First, endogenous CH 4 is detected in maize, 23 alfalfa, 13 and Medicago sativa. 14 In this study, the endogenous levels of CH 4 in young buds significantly exceed that in the senescing condition, which implies that CH 4 may participate in the senescence process of buds.…”
Section: Discussionmentioning
confidence: 99%